The effect of hamstring /quadriceps muscle strength ratio on plantar pressure distribution - A pilot study - Gamze Çobanoğlu; Zeynep Berfu Ecemiş; Batuhan Ünal Şimşek; Nevin A. Güzel; Esedullah Akaras (Turkish Journal of Kinesiology)
The interaction between agonist and antagonist muscles, particularly the quadriceps and hamstrings, is critical in knee joint biomechanics, impacting its stability and functionality during movement. This study investigates the relationship between the hamstring/quadriceps (H/Q) muscle strength ratio and plantar pressure distribution in the foot during walking. Utilizing dynamic pedobarography and isokinetic dynamometry, we assessed 19 male participants (mean age: 25.22±3.33 years; BMI: 22.64±2.39 kg/m²) to measure plantar pressure and muscle strength ratios. Our findings indicate significant correlations between muscle strength imbalances and variations in plantar pressure, suggesting that both the H/Q ratio and individual muscle strengths are influential in foot biomechanics. Specifically, increased hamstring strength relative to the quadriceps was associated with higher plantar pressure on the heel, while a lower H/Q ratio correlated with increased pressure on the forefoot and toes. These insights may underscore the importance of balanced muscle function for maintaining proper gait mechanics and preventing lower extremity injuries. The study highlights the necessity of integrating muscle strength assessments in clinical evaluations to enhance musculoskeletal health and functional mobility.